2012
DOI: 10.3892/mmr.2012.1039
|View full text |Cite
|
Sign up to set email alerts
|

Long-term culture in vitro impairs the immunosuppressive activity of mesenchymal stem cells on T cells

Abstract: Abstract. Improved knowledge of the immunological properties of mesenchymal stem cells (MSCs) creates a potential cell-mediated immunotherapeutic approach for arthritic diseases. The low frequency of MSCs necessitates their in vitro expansion prior to clinical use. As sequential passage has been used as the most popular strategy for expansion of MSCs, the effect of long-term culture on the immunological properties of MSCs is not clear. In this study, we observed that the morphology of MSCs showed the typical c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
40
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 42 publications
(41 citation statements)
references
References 34 publications
1
40
0
Order By: Relevance
“…In this study, high-passage MSCs were used, as they have been shown to produce greater treatment effects than low-passaged cells in rodent models of neurodegenerative diseases (Rossignol et al, 2015). This relationship, however, may not be consistent across different neurological pathologies, and/or species (Li et al, 2012).…”
Section: Discussionmentioning
confidence: 99%
“…In this study, high-passage MSCs were used, as they have been shown to produce greater treatment effects than low-passaged cells in rodent models of neurodegenerative diseases (Rossignol et al, 2015). This relationship, however, may not be consistent across different neurological pathologies, and/or species (Li et al, 2012).…”
Section: Discussionmentioning
confidence: 99%
“…Increasing reports demonstrate that in vitro expansion of MSCs result in senescence of these primary stem cells, and that the differentiation capacity of these stem cells is altered or compromised 22,24 . While currently there are only a few published report with regards to the effects of senescence on MSC immunomodulation 22 , caution should be taken when using MSCs which have been passaged for a prolonged period of time based on our own experience as well (data not shown). Senescence is manifested as a lack of proliferation without cell death, and flattened, enlarged morphology (youthful MSCs are fibroblastic in shape).…”
Section: Discussionmentioning
confidence: 99%
“…One other important aspect which can affect the reproducibility of these assays is the passage number of the MSCs utilized. It has been noted that the mere act of removing MSCs from their physiologic in vivo environment and cryopreservation can compromise function, including immunomodulation 22,23 . Increasing reports demonstrate that in vitro expansion of MSCs result in senescence of these primary stem cells, and that the differentiation capacity of these stem cells is altered or compromised 22,24 .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Mesenchymal stem cells lack expression of major histocompatibility complex class II and costimulatory molecules such as CD80, CD86, or CD40. [29][30][31] In addition, human amniotic mesenchymal stromal cells may modulate immune cell activities and may be transplanted across major histocompatibility complex barriers. [32][33] Amniotic cells may suppress T-cell proliferation because of cell-cell contact and secrete of cytokines.…”
Section: Discussionmentioning
confidence: 99%